Role of Digital Payments in Financial Inclusion and Economic Development in India - Shiksha (International Journal of Advanced Research and Multidisciplinary Trends (IJARMT), 2026)
Digital payments have emerged as a major instrument for promoting financial inclusion and economic development in India. The growth of platforms such as Unified Payments Interface, mobile banking, internet banking, Aadhaar Enabled Payment System, digital wallets, QR code payments and banking correspondent-based services has transformed the way individuals and businesses access financial services. This study explains the role of digital payments in expanding access to banking facilities, reducing dependence on cash, improving transparency and bringing underserved sections into the formal financial system. Digital payments are especially important for rural households, women, farmers, small traders, street vendors and Micro, Small and Medium Enterprises because they provide convenient, low-cost and faster financial transactions. They also support Direct Benefit Transfer by enabling subsidies, pensions, scholarships and welfare payments to reach beneficiaries directly, thereby reducing delays, leakages and middlemen. The study also highlights the contribution of digital payments to economic development through formalization of the economy, tax transparency, reduction in transaction cost, business efficiency, e-commerce growth and better access to credit. However, challenges such as digital illiteracy, poor internet connectivity, cyber fraud, lack of awareness and limited smartphone access continue to restrict full adoption. Overall, digital payments act as a bridge between financial access and inclusive economic growth by strengthening transparency, financial participation and business development in India.